Pengaruh Terpaan Konten Fesyen TikTok di Akun @nazwaadinda_02 terhadap Perilaku Konsumtif Pengikutnya - Aulia, Azzahra; Rusdi, Farid (Prologia, 2022)
The use of social media during the pandemic has increased dramatically, especially among young people. Social media is not only a tool for exchanging messages or just getting information but can be used to transact online. With the convenience obtained by the public in accessing various information and goods on social media, resulting in lifestyle changes that can lead to consumptive attitudes. This study aims to determine the effect of exposure to fesyen content on the @nazwaadinda_02 account on the consumptive attitude of its followers. The approach used is quantitative research. The population in this study are followers of the @nazwaadinda_02 account. The sample taken by the researcher is 100 respondents who are active followers on the Tiktok account @nazwaadinda_02. The technique in determining the sample uses probability sampling technique and the type of simple random sampling technique. Research data collection was carried out using a questionnaire with a Likert scale that used indicators of media exposure theory and consumptive attitudes. A simple linear regression model is used to measure exposure to content with consumptive attitudes. From the results of the research, it can be seen that there is a positive effect of 28% of Exposure to Fesyen Content on Consumptive Attitudes, while the other 72% are influenced by other variables that are not tested. Penggunaan media sosial di masa pandemi meningkat drastis khususnya di kalangan anak muda. Media sosial tidak hanya sebagai alat bertukar pesan atau sekedar mendapatkan informasi tetapi bisa digunakan untuk bertransaksi online. Dengan kemudahan yang didapat oleh masyarakat dalam mengakses berbagai informasi dan barang di media sosial sehingga berakibat perubahan gaya hidup yang dapat menimbulkan sikap konsumtif. Tujuan dari penelitian ini adalah untuk melihat besar pengaruh terpaan konten fesyen di akun @nazwaadinda_02 terhadap sikap konsumtif followersnya. Pendekatan yang diambil adalah penelitian kuantitatif. Populasi yang diambil adalah pengikut dari akun Tiktok @nazwaadinda_02. Sampel yabng diambil oleh peneliti berjumlah 100 responden yang merupakan followers aktif di akun Tiktok @nazwaadinda_02. Teknik dalam menengtukan sampel menggunakan teknik probability sampling dan jenis teknik simple random sampling. Pengumpulan data penelitian dilakukan dengan menggunakan kuisioner dengan skala Likert yang menggunakan indikator teori terpaan media dan sikap konsumtif. Model regresi linear sederhana digunakan untuk mengukur terpaan konten dengan sikap konsumtif. Dari hasil peelitian dapat diketahui bahwa terdapat pengaruh positif sebesar 28% dari Terpaan Konten Fesyen terhadap Sikap Konsumtif sedangkan 72% lainnya dipengaruhi variabel lain yang tidak diuji.